2008
DOI: 10.3748/wjg.14.5316
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic findings can predict the efficacy of leukocytapheresis for steroid-naive patients with moderately active ulcerative colitis

Abstract: AIM:To investigate the therapeutic usefulness of leukocytapheresis (LCAP; Cellsoba) in steroid-naive patients with moderately active ulcerative colitis (UC). METHODS: Eighteen steroid-naive patients with moderately active UC received one LCAP session every week for five consecutive weeks. RESULTS: The remission rate 8 weeks after the last LCAP session was 61.1% (11/18). All three patients with deep ulcers showed worsening after LCAP. For the remaining 15 patients, who had erosions or geographic ulcers, the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Umehara et al. showed that: (i) the clinical course (with the exception of chronic continuous disease); and (ii) endoscopic findings (erosion >geographic ulcer >ulcer) predicted a good outcome . However, BMI was the only significant predictor in our study.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Umehara et al. showed that: (i) the clinical course (with the exception of chronic continuous disease); and (ii) endoscopic findings (erosion >geographic ulcer >ulcer) predicted a good outcome . However, BMI was the only significant predictor in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…Takemoto et al reported that: (i) steroid dependency; and (ii) a high CRP level predicted a good outcome after LCAP therapy (10). Umehara et al showed that: (i) the clinical course (with the exception of chronic continuous disease); and (ii) endoscopic findings (erosion >geographic ulcer >ulcer) predicted a good outcome (18). However, BMI was the only significant…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of Immnopure was also evaluated by comparing pooled results from this study and previous European clinical trials with the abovementioned data from publications concerning treatment with the CA and PET columns. Subgroup analyses of remission rates showed that remission was achieved in 70.4% of patients receiving Immunopure therapy vs. 61.8% to 67.3% of patients using other columns in the moderate disease population and in 69.6% vs. 51.7% to 74.1%, respectively, in the refractory disease population [ 2 , 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. This demonstrates that Immunopure is comparable to existing products in terms of clinical effectiveness in refractory moderate disease.…”
Section: Resultsmentioning
confidence: 99%